ANALISIS PENGEMBANGAN USAHA CHEESE TEA MENGGUNAKAN HAMDI’S METHOD - Agustin, Hamdi; Hamdi, Lathifa Miftahul Jannati; Hamdi, Luthfia Ahluljannati (LP2M Universitas Bina Bangsa, 2024)
This study examines the effectiveness of Hamdi's method which utilizes the gold value (GVM) and gold index (GI) methods to calculate the feasibility study of business on the financial aspect. GVM functions as an alternative to the net present value (NPV) method, while GI acts as a substitute for the profitability index (PI). The purpose was to find out whether the results of Hamdi's method feasibility determination were in line with the conventional approach that uses NPV and PI which are widely applied in the academic world. For this reason, the researcher conducted a case study on the Cheese Tea business in Pekanbaru. The findings show that the results of the feasibility decision using GVM are in line with the NPV calculation, and the results of the feasibility decision using GI are in line with the PI calculation. Thus, Hamdi's method presents a viable option for assessing the feasibility of a business from a financial perspective and contributing to the calculation methods that exist in this domain